Hubungan Antara Dukungan Sosial Dengan Kesiapan Kerja Siswa Kelas X SMK Negeri 1 Donorojo Tahun Pelajaran 2021 / 2022 - Nurdiana, Adinda Ayu (MEDI KONS: Jurnal Prodi Bimbingan dan Konseling UNISRI Surakarta, 2022)
This study aims to determine whether there is a correlation between social support and student work readiness at the tenth grades students of SMK Negeri I Donorojo in 2021/2022 academic year. This research was a correlational quantitative research. The population in this study were all students in class X SMK Negeri I Donorojo with a total number of 230 students. The research sample was 70 students using simple random sampling. Data collection technique was to use a questionnaire and documentation. The questionnaire method was the main method used to obtain data on social support and work readiness. While the documentation method was a method of assistance. In addition, the analytical technique used was a product moment correlation. Based on the results of data analysis on a correlation between social support and student work readiness, it was obtained that the r-count was 0.425. Furthermore, the value of r-count was consulted with the r-table of product moment N=70 and the significance levels of 5% and 1% were 0.235 and 0.306. In fact, the results of the analysis of the data obtained indicated that the r-count was greater than the r-table or 0.235<0.425>0.306. In connection with this, the null hypothesis or Ho which stated that "there is no correlation between social support and student work readiness at the tenth grade students of SMK N I Donorojo in 2021/2022 academic year" was not proven and the work hypothesis or Ha was accepted which stated that "there is a correlation between social support and student work readiness at the tenth grade students of SMKN I Donorojo in 2021/2022 academic year" was accepted at both the level of significant 5% and 1%. Key Words: Relationship, Social Support, Work Readiness